INTERPERSONAL COMMUNICATION IN PUBLIC FORUMS FOR SUSTAINABLE URBAN GOVERNANCE - Muh. Fuad Oktamar Puluco; M. Rizky Saputra; Feiza Salsabila Deka (ADISAM PUBLISHER, 2026)
The challenges of sustaining the quality of life in the city now demand the approach of governance which including citizens in the process of public decision making. Although Palembang City, Indonesia, has been developing the infrastructure and the urban management program, condition of flooding and traffic jam has become a chronic problem. This research explores based on the Aspiration Festival of the Public Aspiration Agency (Badan Aspirasi Masyarakat/BAM) of the House of Representatives of the Republic of Indonesia the role played by the agency in the communication for urban sustainability of governance through public participation. This qualitative case study investigates deliberative processes among participating city, county, and state officials; scholars; community leaders; and citizens. The data included event documentation, government documents, media articles, policy declarations and relevant scientific literature, which were analysed applying thematic analyse. Drawing on DeVito’s Interpersonal Communication Theory, Habermas’ Theory of Communicative Action and Arnstein’s Ladder of Citizen Participation, the research determines openness, empathy, supportiveness, positiveness, and equality as the five major components of interpersonal communication and the factors that contribute to building public trust and consensus in problem solving. Results show that citizens’ concerns can be articulated through an effective interpersonal communication, which can enrich the deliberation and impact on urban policy making. In addition, research findings illustrate that communication is increasingly urban social infrastructure alongside built infrastructure in confronting severe urban problems. In line with these findings the study presents Communicative Sustainable Urban Governance Model (CSUGM) as an integrative model that binds together components such as interpersonal communication, public deliberation, active citizen participation and collaborative governance as a model for sustainable urban development. The research adds to the expanding debates on participatory governance by highlighting communication as a strategic tool to pursue resilient, inclusive and sustainable urban environments.